A method for preparing high thermal conductivity and high strength phenolic resin for copper clad laminate

By using aminolated nano-silver-loaded carbon fibers in copper clad phenolic resin and combining aminolated phenolic resin and epoxy resin, the contradiction between thermal conductivity and strength in the prior art is solved, and a copper clad preparation with high thermal conductivity and high strength is achieved.

CN118909396BActive Publication Date: 2025-04-01JIANG SU YAO HONG ELECTRONICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411062206.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-05
Publication Date
2025-04-01
Estimated Expiration
2044-08-05

AI Technical Summary

Technical Problem

The existing copper clad phenolic resin preparation methods may reduce mechanical strength while improving thermal conductivity, or reduce thermal conductivity while improving mechanical strength, making it difficult to meet the higher requirements of modern electronic equipment for thermal conductivity and strength.

Method used

Aminolated phenolic resin, phenolic resin, and epoxy resin are used as resin matrix, dicyandiamide and 2-methylimidazole are used as curing agents, dimethylformamide is used as organic solvents, and carbon fibers supported by amino-loading nanosilver are added as fillers. The dispersion of nanosilver carbon fibers is improved by carboxylation and amino-modification modification treatment.

Benefits of technology

The high thermal conductivity and high strength of copper clad plate are achieved, the satisfaction of electronic equipment in performance is improved, and the contradiction between thermal conductivity and strength is solved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of phenolic resins, and in particular to a method for preparing a high-thermal-conductivity and high-strength phenolic resin for copper-clad laminates. The present invention uses amino phenolic resin, phenolic resin, and epoxy resin as resin matrix, uses dicyandiamide and 2-methylimidazole as curing agents, dimethylformamide as organic solvent, and adds amino carbon fiber loaded with nanosilver as filler, and prepares a high-thermal-conductivity and high-strength phenolic resin for copper-clad laminates. Carbon fiber has a large specific surface area and fast heat conduction, and can be used as an excellent polymer thermal conductive filler. Nanosilver is loaded on carbon fiber to further enhance the thermal conductivity of the copper-clad laminate. The present invention also uses soybean protein powder to carry out amino modification of phenolic resin, and at this time, the compatibility of amino phenolic resin and amino carbon fiber loaded with nanosilver is good, and the amino carbon fiber loaded with nanosilver has good dispersibility in the phenolic resin system, and at this time, the thermal conductivity of the copper-clad laminate is good and the strength is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of phenolic resins, and in particular to a method for preparing a high-thermal-conductivity and high-strength phenolic resin for a copper-clad laminate. Background Art

[0002] In the field of printed circuit board manufacturing, copper clad laminates are widely used to provide electrical conductivity and mechanical support. As the demand for high performance and high reliability of electronic equipment continues to increase, the performance requirements for copper clad laminates are also increasing. Among them, high thermal conductivity and high strength are two key aspects that affect the performance of copper clad laminates. Phenolic resin has become an ideal copper clad laminate substrate due to its excellent insulation properties, mechanical strength and chemical resistance. However, in order to meet the higher requirements of modern electronic equipment for thermal conductivity and strength, it is necessary to provide a new type of phenolic resin and its preparation method.

[0003] There are some problems with the traditional preparation methods of phenolic resin for copper clad laminates. Some methods may reduce the mechanical strength of the resin while improving thermal conductivity, or reduce thermal conductivity while improving mechanical strength. Therefore, it is an urgent need in the current technical field to find a preparation method for phenolic resin that can improve both thermal conductivity and mechanical strength to meet the ever-increasing demand of electronic equipment for copper clad laminate performance and promote the advancement of copper clad laminate manufacturing technology.

[0004] In order to solve the above problems and improve the thermal conductivity and mechanical strength of copper clad laminates, the present invention provides a method for preparing a high thermal conductivity and high strength phenolic resin for copper clad laminates. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a high thermal conductivity and high strength phenolic resin for copper clad laminates, so as to solve the problems raised in the above background technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A method for preparing a high thermal conductivity and high strength phenolic resin for a copper clad laminate comprises the following steps:

[0008] Step 1: Take hyperbranched polyamide, pyridine, and N,N-dimethylformamide, stir evenly to obtain a mixed solution; take carboxylated nanosilver-loaded carbon fiber, thionyl chloride, and N,N-dimethylformamide, heat to 65-75° C. and stir for 22-26 hours, remove the solvent, add N,N-dimethylformamide, stir at 55-65° C. for 30-40 minutes, add the mixed solution, stir for 22-26 hours, wash, and dry to obtain amino-loaded nanosilver-loaded carbon fiber;

[0009] Step 2: Take the aminated nanosilver-loaded carbon fiber, aminated phenolic resin, phenolic resin, epoxy resin, curing agent, and organic solvent, heat at 85-95° C., mix evenly, and cool to 25-35° C. to obtain a high thermal conductivity and high strength phenolic resin.

[0010] More optimally, the preparation method of the carboxylated nanosilver-loaded carbon fiber is: take glyoxylic acid and deionized water, stir evenly, add sodium bicarbonate solution, add nanosilver-loaded carbon fiber, stir for 2.5-3h, add glutaraldehyde solution, heat to 40-45°C, stir for 2.5-3h, filter, wash, and dry to obtain carboxylated nanosilver-loaded carbon fiber.

[0011] More optimally, the preparation method of the carbon fiber loaded with nanosilver is: take polyacrylonitrile and N,N-dimethylformamide, heat to 55-65°C, add silver nitrate, stir for 2-3h to obtain a spinning solution, and then perform electrostatic spinning; dry, heat to 220-240°C, keep warm for 2-3h, heat to 890-910°C, carbonize for 2-3h, cool, grind, add to sulfuric acid solution, pickle for 22-26h, dry, heat to 940-950°C under nitrogen protection, introduce ammonia, keep warm for 30min, stop introducing nitrogen, cool under ammonia protection to obtain carbon fiber loaded with nanosilver.

[0012] Preferably, the preparation method of the amino phenolic resin comprises the following steps:

[0013] S1: Take a sodium hydroxide solution, heat it to 85-90°C, add soy protein powder, react for 2-3h, and obtain a soy protein powder solution;

[0014] S2: Take phenol, soybean protein powder solution and sodium hydroxide solution, heat to 50-55°C, stir evenly, add formaldehyde, heat to 88-90°C, stir for 40-60min, add formaldehyde and sodium hydroxide solution again, stir at 83-85°C for 30-40min, add formaldehyde, continue stirring at 83-85°C for 30-40min, cool to obtain amino phenolic resin.

[0015] More optimally, the high thermal conductivity and high strength phenolic resin comprises the following components: by weight: 230-240 parts of amino phenolic resin, 60-70 parts of phenolic resin, 100-120 parts of epoxy resin, 70-80 parts of amino carbon fiber loaded with nanosilver, 50-62 parts of curing agent, and 85-90 parts of organic solvent.

[0016] More optimally, the curing agent is any one or more of dicyandiamide and 2-methylimidazole.

[0017] Preferably, the organic solvent is dimethylformamide.

[0018] More optimally, during spinning, the temperature is 45-50°C, the relative humidity is 25-30%RH, the speed is 1.4mL / min, and the voltage is 15kV.

[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0020] (1) The present invention uses amino phenolic resin, phenolic resin, and epoxy resin as resin matrices, uses dicyandiamide and 2-methylimidazole as curing agents, dimethylformamide as an organic solvent, and adds amino carbon fiber loaded with nanosilver as filler to prepare a high thermal conductivity and high strength phenolic resin for copper clad laminates.

[0021] (2) Carbon fiber has a large specific surface area and fast heat conduction, and can be used as an excellent polymer thermal conductive filler. Nanosilver is loaded on carbon fiber, and the thermal conductivity of nanosilver is good, which can further enhance the thermal conductivity of copper-clad laminate. However, the dispersibility of carbon fiber loaded with nanosilver in phenolic resin is not good, which will affect the thermal conductivity and mechanical properties of phenolic resin. In order to solve the above problems, the present invention uses glyoxylic acid to carboxylate the carbon fiber loaded with nanosilver, and then adds hyperbranched polyamide for further amino modification, and a large number of amino groups are grafted on the carbon fiber loaded with nanosilver. The present invention also uses soybean protein powder to carry out amino modification on phenolic resin. At this time, the compatibility of amino phenolic resin and amino carbon fiber loaded with nanosilver is good, and the amino carbon fiber loaded with nanosilver has good dispersibility in the phenolic resin system. At this time, the thermal conductivity of copper-clad laminate is good and the strength is high. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Polyacrylonitrile: item number: P303197, can be purchased from Aladdin; hyperbranched polyamide: model: HyperN101, can be purchased from Wuhan Hyperbranched Resin Technology Co., Ltd.; phenolic resin, solid content 60.11%, viscosity at 25°C is 1150mPa·s, can be purchased from Tongshan Chemical Plant, Gaobeidian City, Hebei Province; epoxy resin: CYD-128 type, can be purchased from Baling Petrochemical Branch of China Petroleum and Chemical Corporation; soy protein powder: protein content is 95%, can be purchased from Shandong Yuwang Ecological Food Co., Ltd.

[0024] Embodiment 1: A method for preparing a high thermal conductivity and high strength phenolic resin for a copper clad laminate, comprising the following steps:

[0025] Step 1: Preparation of carbon fiber loaded with nanosilver:

[0026] Take 3g polyacrylonitrile and 15g N, N-dimethylformamide, heat to 60°C, add 0.3g silver nitrate, stir for 2.5h to obtain a spinning solution, and then perform electrospinning, inhale the spinning solution into a 5mL injection needle, and spin at 47°C, 25% RH relative humidity, 1.4mL / min, and 15kV voltage; dry, heat to 230°C, keep warm for 2.5h, heat to 900°C, carbonize for 2.5h, cool, grind, add to a sulfuric acid solution with a concentration of 1mol / L, pickle for 24h, dry, heat to 945°C under nitrogen protection, pass ammonia, keep warm for 30min, stop passing nitrogen, cool under ammonia protection, and obtain carbon fiber loaded with nanosilver;

[0027] Step 2: Preparation of carboxylation-loaded nanosilver carbon fibers:

[0028] Take 3g of glyoxylic acid and 150mL of deionized water, stir evenly, add 7% sodium bicarbonate solution, adjust the pH value to 6.0, add 12g of carbon fiber loaded with nanosilver, stir for 2.7h, add 50mL of 1% glutaraldehyde solution, heat to 43°C, stir for 2.7h, filter, wash and dry to obtain carboxylated carbon fiber loaded with nanosilver;

[0029] Step 3: Preparation of carbon fiber loaded with nanosilver by amination:

[0030] Take 15g of hyperbranched polyamide, 1mL of pyridine, and 100mL of N,N-dimethylformamide, stir evenly to obtain a mixed solution; take 10g of carboxylated nanosilver-loaded carbon fiber, 150mL of thionyl chloride, and 20mL of N,N-dimethylformamide, heat to 70°C and stir for 24h, remove the solvent, add 200mL of N,N-dimethylformamide, stir at 60°C for 35min, add the mixed solution, stir for 24h, wash, and dry to obtain amino-loaded nanosilver-loaded carbon fiber;

[0031] Step 4: Preparation of amino phenolic resin:

[0032] Take 200g of 10% sodium hydroxide solution, heat it to 88°C, add 100g of soy protein powder, react for 2.5h, and obtain a soy protein powder solution;

[0033] Take 80g of phenol, 10g of soy protein powder solution, and 15g of 10% sodium hydroxide solution by mass, heat to 52°C, stir evenly, add 100g of formaldehyde, heat to 89°C, stir for 50min, add 55g of formaldehyde and 15g of 10% sodium hydroxide solution by mass, stir at 85°C for 35min, add 40g of formaldehyde, continue stirring at 84°C for 35min, cool, and obtain an amino phenolic resin;

[0034] Step 5: Preparation of high thermal conductivity and high strength phenolic resin for copper clad laminate:

[0035] Take the aminated nanosilver-loaded carbon fiber, aminated phenolic resin, phenolic resin, epoxy resin, dicyandiamide, 2-methylimidazole, and organic solvent dimethylformamide, heat at 90° C., mix evenly, and cool to 30° C. to obtain a phenolic resin with high thermal conductivity and high strength;

[0036] The high thermal conductivity and high strength phenolic resin comprises the following components: by weight: 235 parts of amino phenolic resin, 65 parts of phenolic resin, 110 parts of epoxy resin, 75 parts of amino carbon fiber loaded with nanosilver, 55 parts of dicyandiamide, 0.35 parts of 2-methylimidazole, and 88 parts of organic solvent dimethylformamide.

[0037] Embodiment 2: A method for preparing a high thermal conductivity and high strength phenolic resin for a copper clad laminate, comprising the following steps:

[0038] Step 1: Preparation of carbon fiber loaded with nanosilver:

[0039] Take 3g polyacrylonitrile and 15g N, N-dimethylformamide, heat to 55°C, add 0.3g silver nitrate, stir for 3h to obtain a spinning solution, and then perform electrostatic spinning, suck the spinning solution into a 5mL injection needle, and spin at 45°C, 25% RH relative humidity, 1.4mL / min, and 15kV voltage; dry, heat to 220°C, keep warm for 2h, heat to 890°C, carbonize for 3h, cool, grind, add to a sulfuric acid solution with a concentration of 1mol / L, pickle for 22h, dry, heat to 940°C under nitrogen protection, pass ammonia, keep warm for 30min, stop passing nitrogen, cool under ammonia protection, and obtain carbon fiber loaded with nanosilver;

[0040] Step 2: Preparation of carboxylation-loaded nanosilver carbon fibers:

[0041] Take 3g of glyoxylic acid and 150mL of deionized water, stir evenly, add 7% sodium bicarbonate solution, adjust the pH value to 6.0, add 12g of carbon fiber loaded with nanosilver, stir for 2.5h, add 50mL of 1% glutaraldehyde solution, heat to 40°C, stir for 2.5h, filter, wash and dry to obtain carboxylated carbon fiber loaded with nanosilver.

[0042] Step 3: Preparation of carbon fiber loaded with nanosilver by amination:

[0043] Take 15g of hyperbranched polyamide, 1mL of pyridine, and 100mL of N,N-dimethylformamide, stir evenly to obtain a mixed solution; take 10g of carboxylated nanosilver-loaded carbon fiber, 150mL of thionyl chloride, and 20mL of N,N-dimethylformamide, heat to 65°C and stir for 22h, remove the solvent, add 200mL of N,N-dimethylformamide, stir at 55°C for 30min, add the mixed solution, stir for 22h, wash, and dry to obtain amino-loaded nanosilver-loaded carbon fiber;

[0044] Step 4: Preparation of amino phenolic resin:

[0045] Take 200g of 10% sodium hydroxide solution, heat it to 85°C, add 100g of soy protein powder, react for 2h, and obtain a soy protein powder solution;

[0046] Take 80g of phenol, 10g of soy protein powder solution, and 15g of 10% sodium hydroxide solution by mass, heat to 50°C, stir evenly, add 100g of formaldehyde, heat to 88°C, stir for 40min, add 55g of formaldehyde and 15g of 10% sodium hydroxide solution by mass, stir at 83°C for 30min, add 40g of formaldehyde, continue stirring at 83°C for 30min, cool, and obtain an amino phenolic resin;

[0047] Step 5: Preparation of high thermal conductivity and high strength phenolic resin for copper clad laminate:

[0048] Take the aminated nanosilver-loaded carbon fiber, aminated phenolic resin, phenolic resin, epoxy resin, dicyandiamide, 2-methylimidazole, and organic solvent dimethylformamide, heat at 85° C., mix evenly, and cool to 25° C. to obtain a phenolic resin with high thermal conductivity and high strength;

[0049] The high thermal conductivity and high strength phenolic resin comprises the following components: by weight: 230 parts of amino phenolic resin, 60 parts of phenolic resin, 100 parts of epoxy resin, 70 parts of amino carbon fiber loaded with nanosilver, 50 parts of dicyandiamide, 0.3 parts of 2-methylimidazole, and 85 parts of organic solvent dimethylformamide.

[0050] Embodiment 3: A method for preparing a high thermal conductivity and high strength phenolic resin for a copper clad laminate, comprising the following steps:

[0051] Step 1: Preparation of carbon fiber loaded with nanosilver:

[0052] Take 3g polyacrylonitrile and 15g N, N-dimethylformamide, heat to 65°C, add 0.3g silver nitrate, stir for 3h to obtain a spinning solution, and then perform electrostatic spinning, suck the spinning solution into a 5mL injection needle, and spin at 50°C, 30% RH relative humidity, 1.4mL / min, and 15kV voltage; dry, heat to 240°C, keep warm for 3h, heat to 910°C, carbonize for 3h, cool, grind, add to a sulfuric acid solution with a concentration of 1mol / L, pickle for 26h, dry, heat to 950°C under nitrogen protection, pass ammonia, keep warm for 30min, stop passing nitrogen, cool under ammonia protection, and obtain carbon fiber loaded with nanosilver;

[0053] Step 2: Preparation of carboxylation-loaded nanosilver carbon fibers:

[0054] Take 3g of glyoxylic acid and 150mL of deionized water, stir evenly, add 7% sodium bicarbonate solution, adjust the pH value to 6.5, add 12g of carbon fiber loaded with nanosilver, stir for 3h, add 50mL of 1% glutaraldehyde solution, heat to 45°C, stir for 3h, filter, wash and dry to obtain carboxylated carbon fiber loaded with nanosilver;

[0055] Step 3: Preparation of carbon fiber loaded with nanosilver by amination:

[0056] Take 15g of hyperbranched polyamide, 1mL of pyridine, and 100mL of N,N-dimethylformamide, stir evenly to obtain a mixed solution; take 10g of carboxylated nanosilver-loaded carbon fiber, 150mL of thionyl chloride, and 20mL of N,N-dimethylformamide, heat to 75°C and stir for 26h, remove the solvent, add 200mL of N,N-dimethylformamide, stir at 65°C for 40min, add the mixed solution, stir for 26h, wash, and dry to obtain amino-loaded nanosilver-loaded carbon fiber;

[0057] Step 4: Preparation of amino phenolic resin:

[0058] Take 200g of 10% sodium hydroxide solution, heat it to 90°C, add 100g of soy protein powder, and react for 3h to obtain a soy protein powder solution;

[0059] Take 80g of phenol, 10g of soy protein powder solution, and 15g of 10% sodium hydroxide solution by mass, heat to 55°C, stir evenly, add 100g of formaldehyde, heat to 90°C, stir for 60min, add 55g of formaldehyde and 15g of 10% sodium hydroxide solution by mass, stir at 85°C for 40min, add 40g of formaldehyde, continue stirring at 85°C for 40min, cool, and obtain an amino phenolic resin;

[0060] Step 5: Preparation of high thermal conductivity and high strength phenolic resin for copper clad laminate:

[0061] Take the aminated nanosilver-loaded carbon fiber, aminated phenolic resin, phenolic resin, epoxy resin, dicyandiamide, 2-methylimidazole, and organic solvent dimethylformamide, heat at 95° C., mix evenly, and cool to 35° C. to obtain a phenolic resin with high thermal conductivity and high strength;

[0062] The high thermal conductivity and high strength phenolic resin comprises the following components: by weight: 240 parts of amino phenolic resin, 70 parts of phenolic resin, 120 parts of epoxy resin, 80 parts of amino carbon fiber loaded with nanosilver, 60 parts of dicyandiamide, 0.4 parts of 2-methylimidazole, and 90 parts of organic solvent dimethylformamide.

[0063] Comparative Example 1: No nanosilver loading, the rest is the same as Example 1:

[0064] Step 1: Preparation of carbon fiber:

[0065] Take 3g polyacrylonitrile and 15g N, N-dimethylformamide, heat to 60°C, stir for 2.5h to obtain a spinning solution, and then perform electrospinning, suck the spinning solution into a 5mL injection needle, and spin at 47°C, 25% RH relative humidity, 1.4mL / min, and 15kV voltage; dry, heat to 230°C, keep warm for 2.5h, heat to 900°C, carbonize for 2.5h, cool, grind, add to a sulfuric acid solution with a concentration of 1mol / L, pickle for 24h, dry, heat to 945°C under nitrogen protection, pass ammonia, keep warm for 30min, stop passing nitrogen, cool under ammonia protection to obtain carbon fiber;

[0066] Step 2: Preparation of carboxylated carbon fibers:

[0067] Take 3g of glyoxylic acid and 150mL of deionized water, stir evenly, add 7% sodium bicarbonate solution, adjust the pH value to 6.0, add 12g of carbon fiber loaded with nanosilver, stir for 2.7h, add 50mL of 1% glutaraldehyde solution, heat to 43°C, stir for 2.7h, filter, wash and dry to obtain carboxylated carbon fiber;

[0068] Step 3: Preparation of amino carbon fiber:

[0069] Take 15g of hyperbranched polyamide, 1mL of pyridine, and 100mL of N,N-dimethylformamide, stir evenly to obtain a mixed solution; take 10g of carboxylated nanosilver-loaded carbon fiber, 150mL of thionyl chloride, and 20mL of N,N-dimethylformamide, heat to 70°C and stir for 24h, remove the solvent, add 200mL of N,N-dimethylformamide, stir at 60°C for 35min, add the mixed solution, stir for 24h, wash, and dry to obtain amino carbon fiber;

[0070] Step 4: Preparation of amino phenolic resin:

[0071] Take 200g of 10% sodium hydroxide solution, heat it to 88°C, add 100g of soy protein powder, react for 2.5h, and obtain a soy protein powder solution;

[0072] Take 80g of phenol, 10g of soy protein powder solution, and 15g of 10% sodium hydroxide solution by mass, heat to 52°C, stir evenly, add 100g of formaldehyde, heat to 89°C, stir for 50min, add 55g of formaldehyde and 15g of 10% sodium hydroxide solution by mass, stir at 85°C for 35min, add 40g of formaldehyde, continue stirring at 84°C for 35min, cool, and obtain an amino phenolic resin;

[0073] Step 5: Preparation of high thermal conductivity and high strength phenolic resin for copper clad laminate:

[0074] Take amino carbon fiber, amino phenolic resin, phenolic resin, epoxy resin, dicyandiamide, 2-methylimidazole, and organic solvent dimethylformamide, heat at 90° C., mix evenly, and cool to 30° C. to obtain high thermal conductivity and high strength phenolic resin;

[0075] The high thermal conductivity and high strength phenolic resin comprises the following components: by weight: 235 parts of amino phenolic resin, 65 parts of phenolic resin, 110 parts of epoxy resin, 75 parts of amino carbon fiber, 55 parts of dicyandiamide, 0.35 parts of 2-methylimidazole, and 88 parts of organic solvent dimethylformamide.

[0076] Comparative Example 2: The carbon fiber loaded with nanosilver is not subjected to amination treatment, and the rest is the same as Example 1:

[0077] Step 1: Preparation of carbon fiber loaded with nanosilver:

[0078] Take 3g polyacrylonitrile and 15g N, N-dimethylformamide, heat to 60°C, add 0.3g silver nitrate, stir for 2.5h to obtain a spinning solution, and then perform electrospinning, inhale the spinning solution into a 5mL injection needle, and spin at 47°C, 25% RH relative humidity, 1.4mL / min, and 15kV voltage; dry, heat to 230°C, keep warm for 2.5h, heat to 900°C, carbonize for 2.5h, cool, grind, add to a sulfuric acid solution with a concentration of 1mol / L, pickle for 24h, dry, heat to 945°C under nitrogen protection, pass ammonia, keep warm for 30min, stop passing nitrogen, cool under ammonia protection, and obtain carbon fiber loaded with nanosilver;

[0079] Step 2: Preparation of amino phenolic resin:

[0080] Take 200g of 10% sodium hydroxide solution, heat it to 88°C, add 100g of soy protein powder, react for 2.5h, and obtain a soy protein powder solution;

[0081] Take 80g of phenol, 10g of soy protein powder solution, and 15g of 10% sodium hydroxide solution by mass, heat to 52°C, stir evenly, add 100g of formaldehyde, heat to 89°C, stir for 50min, add 55g of formaldehyde and 15g of 10% sodium hydroxide solution by mass, stir at 85°C for 35min, add 40g of formaldehyde, continue stirring at 84°C for 35min, cool, and obtain an amino phenolic resin;

[0082] Step 3: Preparation of high thermal conductivity and high strength phenolic resin for copper clad laminate:

[0083] Take carbon fiber loaded with nanosilver, amino phenolic resin, phenolic resin, epoxy resin, dicyandiamide, 2-methylimidazole, and organic solvent dimethylformamide, heat at 90° C., mix evenly, and cool to 30° C. to obtain a phenolic resin with high thermal conductivity and high strength;

[0084] The high thermal conductivity and high strength phenolic resin comprises the following components: by weight: 235 parts of amino phenolic resin, 65 parts of phenolic resin, 110 parts of epoxy resin, 75 parts of carbon fiber loaded with nanosilver, 55 parts of dicyandiamide, 0.35 parts of 2-methylimidazole, and 88 parts of organic solvent dimethylformamide.

[0085] Comparative Example 3: The phenolic resin is not subjected to amination treatment, and the rest is the same as Example 1:

[0086] Step 1: Preparation of carbon fiber loaded with nanosilver:

[0087] Take 3g polyacrylonitrile and 15g N, N-dimethylformamide, heat to 60°C, add 0.3g silver nitrate, stir for 2.5h to obtain a spinning solution, and then perform electrospinning, inhale the spinning solution into a 5mL injection needle, and spin at 47°C, 25% RH relative humidity, 1.4mL / min, and 15kV voltage; dry, heat to 230°C, keep warm for 2.5h, heat to 900°C, carbonize for 2.5h, cool, grind, add to a sulfuric acid solution with a concentration of 1mol / L, pickle for 24h, dry, heat to 945°C under nitrogen protection, pass ammonia, keep warm for 30min, stop passing nitrogen, cool under ammonia protection, and obtain carbon fiber loaded with nanosilver;

[0088] Step 2: Preparation of carboxylation-loaded nanosilver carbon fibers:

[0089] Take 3g of glyoxylic acid and 150mL of deionized water, stir evenly, add 7% sodium bicarbonate solution, adjust the pH value to 6.0, add 12g of carbon fiber loaded with nanosilver, stir for 2.7h, add 50mL of 1% glutaraldehyde solution, heat to 43°C, stir for 2.7h, filter, wash and dry to obtain carboxylated carbon fiber loaded with nanosilver.

[0090] Step 3: Preparation of carbon fiber loaded with nanosilver by amination:

[0091] Take 15g of hyperbranched polyamide, 1mL of pyridine, and 100mL of N,N-dimethylformamide, stir evenly to obtain a mixed solution; take 10g of carboxylated nanosilver-loaded carbon fiber, 150mL of thionyl chloride, and 20mL of N,N-dimethylformamide, heat to 70°C and stir for 24h, remove the solvent, add 200mL of N,N-dimethylformamide, stir at 60°C for 35min, add the mixed solution, stir for 24h, wash, and dry to obtain amino-loaded nanosilver-loaded carbon fiber;

[0092] Step 4: Preparation of high thermal conductivity and high strength phenolic resin for copper clad laminate:

[0093] Take the aminated nanosilver-loaded carbon fiber, phenolic resin, epoxy resin, dicyandiamide, 2-methylimidazole, and organic solvent dimethylformamide, heat at 90° C., mix evenly, and cool to 30° C. to obtain a phenolic resin with high thermal conductivity and high strength;

[0094] The high thermal conductivity and high strength phenolic resin comprises the following components: by weight: 300 parts of phenolic resin, 110 parts of epoxy resin, 75 parts of amino-loaded nanosilver carbon fiber, 55 parts of dicyandiamide, 0.35 parts of 2-methylimidazole, and 88 parts of organic solvent dimethylformamide.

[0095] experiment:

[0096] The high thermal conductivity and high strength phenolic resin prepared in Examples 1-3 and Comparative Examples 1-3 was used to impregnate 7628 glass cloth, and dried at 130°C to obtain a prepreg. Three prepregs were overlapped, and electrolytic copper foil with a thickness of 35 μm was covered on the upper and lower surfaces. The prepreg was heated at 220°C at a temperature of 25 kg / cm 2 The copper clad laminate was obtained by hot pressing for 180 minutes under a pressure of . The performance of each copper clad laminate was tested. The copper clad laminates prepared in Examples 1 to 6 were taken and the performance was tested according to the corresponding method of IPC-TM-650. The peel strength of the copper clad laminate was tested. The thermal conductivity of the copper clad laminate was tested with reference to D5470. The obtained data are shown in the following table:

[0097] Peel strength / (1b / in) Thermal conductivity / (W / (m·k)) Example 1 14.2 3.2 Example 2 14.0 3.1 Example 3 14.3 3.2 Comparative Example 1 13.7 2.2 Comparative Example 2 12.3 2.8 Comparative Example 3 12.5 2.9

[0098] Conclusion: From the comparison of the data in the table, it can be seen that in Comparative Example 1, the thermal conductivity of the copper clad laminate is reduced without loading nanosilver. In Comparative Example 2, the carbon fiber loaded with nanosilver is not subjected to amination treatment, and the dispersion of the carbon fiber loaded with nanosilver in the phenolic resin is not good, and the thermal conductivity and peel strength of the copper clad laminate are reduced. In Comparative Example 3, the phenolic resin is not subjected to amination treatment, and the peel strength of the copper clad laminate is significantly reduced, which is only 12.51b / in. The high thermal conductivity and high strength phenolic resin prepared by the method provided by the present invention has better performance.

[0099] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a high thermal conductivity and high strength phenolic resin for copper clad laminates, characterized in that: The following steps are involved: Step 1: Take hyperbranched polyamide, pyridine, and N,N-dimethylformamide, stir evenly to obtain a mixed solution; take carboxylated nanosilver-loaded carbon fiber, thionyl chloride, and N,N-dimethylformamide, heat to 65-75° C. and stir for 22-26 hours, remove the solvent, add N,N-dimethylformamide, stir at 55-65° C. for 30-40 minutes, add the mixed solution, stir for 22-26 hours, wash, and dry to obtain amino-loaded nanosilver-loaded carbon fiber; Step 2: Take the aminated nanosilver-loaded carbon fiber, aminated phenolic resin, phenolic resin, epoxy resin, curing agent, and organic solvent, heat at 85-95° C., mix evenly, and cool to 25-35° C. to obtain a high thermal conductivity and high strength phenolic resin; The preparation method of the carboxylated nanosilver-loaded carbon fiber is as follows: taking glyoxylic acid and deionized water, stirring evenly, adding sodium bicarbonate solution, adding nanosilver-loaded carbon fiber, stirring for 2.5-3h, adding glutaraldehyde solution, heating to 40-45°C, stirring for 2.5-3h, filtering, washing, and drying to obtain the carboxylated nanosilver-loaded carbon fiber; The preparation method of the amino phenolic resin is: The following steps are involved: S1: Take a sodium hydroxide solution, heat it to 85-90°C, add soy protein powder, react for 2-3h, and obtain a soy protein powder solution; S2: Take phenol, soybean protein powder solution and sodium hydroxide solution, heat to 50-55°C, stir evenly, add formaldehyde, heat to 88-90°C, stir for 40-60min, add formaldehyde and sodium hydroxide solution again, stir at 83-85°C for 30-40min, add formaldehyde, continue stirring at 83-85°C for 30-40min, cool to obtain amino phenolic resin; The high thermal conductivity and high strength phenolic resin comprises the following components: by weight: 230-240 parts of amino phenolic resin, 60-70 parts of phenolic resin, 100-120 parts of epoxy resin, 70-80 parts of amino carbon fiber loaded with nanosilver, 50-62 parts of curing agent, and 85-90 parts of organic solvent.

2. The method for preparing a high thermal conductivity and high strength phenolic resin for copper clad laminate according to claim 1, characterized in that: The curing agent is any one or more of dicyandiamide and 2-methylimidazole.

3. The method for preparing a high thermal conductivity and high strength phenolic resin for copper clad laminate according to claim 1, characterized in that: The organic solvent is dimethylformamide.

4. The method for preparing a high thermal conductivity and high strength phenolic resin for copper clad laminate according to claim 1, characterized in that: During spinning, the temperature was 45-50° C., the relative humidity was 25-30% RH, the speed was 1.4 mL / min, and the voltage was 15 kV.

Citation Information

Patent Citations

  • Modified phenolic resin adhesive

    CN107312481A

  • Preparation method of carbon nanotube reinforced phenolic aldehyde-organosilicon resin based carbon fiber composite material

    CN111234451A